Native Sovereignty and French Justice in Early Canada - Dickinson, John A. (Essays in the History of Canadian Law, 1994)
As native territorial claims and the issue of self-government become increasingly important on the Canadian political agenda, questions of native sovereignty in historical context take on new meaning. The United States recognizes Indian nations as sovereign entities to whom the federal government is legally bound to carry out its ‘trust responsibility’¹ Canada has not followed this lead, and although some recent decisions – notably the Sparrow (1987) and Sioui (1990) cases – have been more generous in recognizing native claims,² aboriginal rights are never taken for granted. In recent Quebec cases, for example, the Crown has tried to prove that